Cryptococcus neoformans Δsgl1 Vaccination Requires Either CD4+ or CD8+ T Cells for Complete Host Protection - Normile, Tyler G.; Rella, Antonella; Del Poeta, Maurizio (Frontiers in Cellular and Infection Microbiology, 2021)
Cryptococcus neoformans is a fungal pathogen causing a life-threatening meningoencephalitis in susceptible individuals. Fungal vaccine development has been hampered by the fact that cryptococcosis occurs during immunodeficiency. We previously reported that a C. neoformans mutant (delta-sgl1) accumulating sterylglucosides (SGs) is avirulent and provides complete protection to WT challenge, even under CD4+ T cell depletion, an immunodeficient condition associated with cryptococcosis. Here, we found high levels of SGs in lungs post immunization with sgl1 that decreased upon fungal clearance. During the immunization period, Th1 cytokines increased whereas Th2 cytokines decreased, coinciding with a large recruitment of leukocytes to the lungs. Depletion of B or CD8+ T cells did not affect delta-sgl1 clearance or protection from WT challenge. Although CD4+ T cell depletion affected clearance, mice were still protected. Protection was lost only when both CD4+ and CD8+ T cells were depleted, highlighting a previously unexplored role of fungal-derived SGs as an immunoadjuvant for protection against cryptococcosis.